Efficacy of injection of steroids for lateral epicondylitis - Maharjan, R; Gurung, G (Journal of Institute of Medicine Nepal, 2011)
Introduction: Lateral epicondylitis (Tennis elbow) is one of the most common lesions of the arm. Corticosteroid injection has been described as one of the treatment modalities for this disorder with variable clinical benefit. The purpose of this study was to analyze the short-term and long-term effects of the local injection of methylprednisolone to treat lateral epicondylitis. Methods: A prospective comparative study was carried out in the Department of Orthopaedics in Bir Hospital from October 2009 to February 2011. Study was undertaken in 40 patients to analyze the short-term and long-term effects of the local injection of methylprednisolone for the treatment of lateral epicondylitis. Twenty patients in each group were included in the study. Patients assigned to experimental group received a single injection of 1 percent lidocaine with forty milligrams of methylprednisolone and control group received a single injection of 1 percent lidocaine with saline solution. Results: Corticosteroid injection gave better pain relief in a shorter time than the placebo group. Pain was significantly improved in steroid group in comparison to placebo group till third successive follow ups with maximum improvement at eighteen weeks (p=0.000). However, the groups did not differ with regards to pain at six months as determined with a clinical pain score and visual analogue scale. Conclusions: Local injections of steroids provide rapid pain relief but only short-term benefits in the treatment of lateral epicondylitis. Key word: Epicondylities; Steroid injection; tennis elbow DOI: http://dx.doi.org/10.3126/joim.v32i3.4958 Journal of Institute of Medicine, December, 2010; 32:3 34-38